THE TEACHERS' CLINIC. - Garner, S. Paul (The Accounting Review, 1947)
Abstract Beginning instructors are usually assigned to the elementary course in order to obtain their experience. The large volume of students is also found at this level. The intermediate course presents a somewhat similar problem, although it is less acute. Generally, the courses above the intermediate level are in the hands of experienced instructors. The writer believes that all the ability and skills an instructor can command are required at the first level. If the student fails to learn the fundamentals well, difficulties in more advanced courses may be due to the structural weakness of the introductory background rather than to the advanced course per se. The problems of the beginning instructor are increased not only by the range of interest and ability to grasp the subject but also by sheer numbers. In advanced courses, however, there is the advantage of selection. The suggestions offered here are primarily to help the beginner. They are not intended to be complete. Also they are confined to the elementary course, although they may be applied also to the more advanced classes.